277 Tunable White Light for Elders (TWLITE): A feasibility study of a home-based sleep intervention. (3rd May 2021) - Jones, Carolyn; Reynolds, Christina; Olson, Randall; Bontrager, Ashten; Lambert, Sophia; Balba, Nadir; Weymann, Kristianna; Kaye, Jeffrey; Wilkerson, Andrea; Elliott, Jonathan; Lim, Miranda
Abstract: Introduction: Sleep disturbances are common in elderly patients and may contribute to disease progression in certain populations (e.g., Alzheimer's Disease). Light therapy is a simple and cost-effective intervention to improve sleep. Primary barriers to light therapy are 1) poor acceptability to use of devices and 2) inflexibility of current devices to deliver beyond a fixed spectrum and throughout the entirety of the day. However, dynamic, tunable lighting integrated into the native home lighting system can maximize short-wavelength light in the morning and minimize short-wavelength light in the evening, thus entraining circadian rhythms and treating sleep disturbances, and overcome these limitations. We determined the feasibility of implementing a whole-home tunable lighting system as a potential sleep intervention. Methods: Tunable LED lights were installed throughout the homes of healthy older adults already enrolled in an existing study with embedded home assessment platforms (ORCATECH study; n=4 subjects in n=3 homes). In ORCATECH, continuous data on room location, activity, sleep, and general health parameters are collected at minute-to-minute resolution over months to years of participation. This single arm longitudinal design collected participants' light usage in addition to ORCATECH outcome measures. Primary outcomes for this pilot study included the feasibility and patient acceptability. Exploratory outcomes were sleep metrics (sleep time, latency, efficiency), mobility (room transitions and actigraphy), and overall health indices (weekly body weight, self-report general health questionnaires) both pre- and post-intervention. Results: Two subjects terminated the study citing technical difficulties with the lights and a preference for brighter illumination. Of the remaining 2 participants, sleep metrics were explored over a 12-month period spanning pre- and post-installation of lights. Nightly duration in bed was compared with minute-to-minute room entry data and actigraphy with high inter-measure reliability. Conclusion: These data support that tunable whole-home lighting systems are reasonably acceptable and feasibly implemented using an automated platform for continuous data collection. Quantification of sleep over long periods of time is robust and reliable in the home environment of elderly subjects. These results will inform implementation of future large-scale lighting intervention studies in patients at risk for developing Alzheimer's Disease. Support (if any): Hartford Gerontological Center Interprofessional Award, Pacific Northwest National Laboratory, OHSU ORCATECH